Employees’ Work Quality: The Role of Work Comfort and Completeness of Company Facilities - Sutanto, Eddy Madiono; Subijanto, Mellisa (Fakultas Ekonomi dan Bisnis, Telkom University., 2024)
Viewed in this world, humans were the most important aspect of a company, and humans had an important role in advancing and improving the company. Therefore, it was necessary to see how much comfort and facilities factors can affect the employees’ work quality. This study was conducted to see whether or not there was an influence of work comfort and completeness of company facilities on employees’ work quality, with work motivation as the intervening variable. This research used quantitative research, which involved 148 respondents. Data processing in this study used SmartPLS. From the results of data processing from respondents' answers, it concluded that (1) Work comfort had a significant positive effect on work motivation, (2) Work comfort had no significant effect on employees’ work quality, (3) Company facilities completeness had a positive significant effect on work motivation, (4) Completeness of company facilities had no significant effect on employees’ work quality (5) Work motivation had a significant positive effect on employees’ work quality, (6) Work motivation did not mediate significantly the relationship between work comfort on work quality, and (7) Work motivation did not mediate significantly the relationship between completeness of company facilities on work quality. In order to enhance the employees’ work quality, the company management should consider using something other than the work comfort and the completeness of working facilities to increase employees' work motivation as the Two Factors Motivation Theory of Frederick Herzberg. Keywords— Work Comfort; Completeness of Company Facilities; Employees’ Work Quality; Work Motivation